Evaluation of Antioxidant and Antinociceptive Properties of Methanolic Extract of Clerodendrum viscosum Vent. - Rahman, Md Mostafizur; Rumzhum, Nowshin N; Zinna, Kudrat-E-Khuda (Stamford Journal of Pharmaceutical Sciences, 2011)
The PDF for this article was updated on 18/11/2011. NN Rumzhum and K Zinna were added as authors on 18/11/2011. The methanolic extract of Clerodendrum viscosum vent. (Verbenaceae) was evaluated for in vitro antioxidant activity by determination of total antioxidant capacity, assay of nitric oxide scavenging activity and reducing power test and in vivo antinociceptive effect in acetic acid induced writhing model in swiss albino mice. The results revealed the presence of pronounced antioxidant property as compared with ascorbic acid used as standard and a dose-dependent (250 and 500 mg/kg) analgesic effect in Clerodendrum viscosum vent. The antioxidant and antinociceptive activities obtained seem to be in good accordance with the traditional uses of Clerodendrum viscosum. Key words: Clerodendrum viscosum; Verbenaceae; Antioxidant; Ascorbic acid; Antinociceptive; Swiss albino mice DOI: http://dx.doi.org/10.3329/sjps.v4i1.8873 SJPS 2011; 4(1): 74-78